BCR Affinity Influences T-B Interactions and B Cell Development in Secondary Lymphoid Organs - Wishnie, Alec J.; Chwat-Edelstein, Tzippora; Attaway, Mary; Vuong, Bao Q. (Frontiers in Immunology, 2021)
B cells produce high-affinity immunoglobulins (Igs), or antibodies, to eliminate foreign pathogens. Mature, naïve B cells expressing an antigen-specific cell surface Ig, or B cell receptor (BCR), are directed toward either an extrafollicular (EF) or germinal center (GC) response upon antigen binding. B cell interactions with CD4+ pre-T follicular helper (pre-Tfh) cells at the T-B border and effector Tfh cells in the B cell follicle and GC control B cell development in response to antigen. Here, we review recent studies demonstrating the role of B cell receptor (BCR) affinity in modulating T-B interactions and the subsequent differentiation of B cells in the EF and GC response. Overall, these studies demonstrate that B cells expressing high affinity BCRs preferentially differentiate into antibody secreting cells (ASCs) while those expressing low affinity BCRs undergo further affinity maturation or differentiate into memory B cells (MBCs).